Аналіз методів криптозахисту даних в хмарних обчисленнях - Якдува Усман Хассан (My University, 2023)
The object of research is the processes of functioning of telecommunication systems using cloud computing. The subject of the research is the characteristics of telecommunication systems using cloud computing. The purpose of the work is to analyze the architecture and technology parameters of telecommunication systems using cloud computing, as well as to improve the methods of information protection of such systems. Research methods – empirical analysis, comparison, analytical modeling. Today, the topic of data protection in cloud computing networks is relevant, as nowadays there is a significant increase in the number of users and information flows in cloud computing systems. The paper analyzes modern cloud computing systems, their threats and vulnerabilities. It is proposed to improve the method of information protection of data in cloud computing. A performance study of the data protection algorithm in cloud storage was performed. Recommendations for increasing the protection of cloud computing systems have been developed.
Keywords: information security; cloud computing; threats; vulnerabilities; Data Audit; Data Protection; performance